2019
DOI: 10.3390/jcm8060890
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Antidepressant Effects of Oltipraz on Neuropathic Pain in Mice by Modulating Microglial Activation

Abstract: Nerve injury provokes microglial activation, contributing to the sensory and emotional disorders associated with neuropathic pain that do not completely resolve with treatment. In C57BL/6J mice with neuropathic pain induced by chronic constriction of the sciatic nerve (CCI), we evaluated the effects of oltipraz, an antioxidant and anticancer compound, on (1) allodynia and hyperalgesia, (2) microglial activation and pain signaling pathways, (3) oxidative stress, and (4) depressive-like behaviors. Twenty-eight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 62 publications
(95 reference statements)
4
38
0
Order By: Relevance
“…However, microglia are not activated in the spinal cord after paclitaxel treatment, thus excluding their role in the pathogenesis of PINP [ 40 ]. In a very recent study, Díaz et al claimed that oltipraz possesses analgesic and antidepressant effects in a mouse model of neuropathic pain induced by chronic constriction of the sciatic nerve [ 41 ]. They found that the inhibition of microglial activation and induction of the Nrf2/HO-1-signaling pathway in the hippocampus and/or prefrontal cortex contributes to the protective effects of oltipraz.…”
Section: Discussionmentioning
confidence: 99%
“…However, microglia are not activated in the spinal cord after paclitaxel treatment, thus excluding their role in the pathogenesis of PINP [ 40 ]. In a very recent study, Díaz et al claimed that oltipraz possesses analgesic and antidepressant effects in a mouse model of neuropathic pain induced by chronic constriction of the sciatic nerve [ 41 ]. They found that the inhibition of microglial activation and induction of the Nrf2/HO-1-signaling pathway in the hippocampus and/or prefrontal cortex contributes to the protective effects of oltipraz.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, systemic and central nervous system inflammatory responses promoted by sleep disturbances increase pain sensitivity through multiple signaling pathways. [24][25][26][27] In addition, long-term poor sleep quality can continuously activate the hypothalamus-pituitaryadrenal axis, which produces a large amount of corticotropin and cortisol. 28 Study on healthy volunteers has reported that high corticosteroid levels in the body could enhance pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…34 Furthermore, persistent neuropathic pain is associated with emotional disorders, such as anxiety and depression. 1,2 Previous reports using rodents have shown that pain lasting more than 4 weeks induces emotional dysfunction, such as anxiety or depression-like behavior. 35,36 In the present work, depression-like behavior was observed in female Wistar rats 3 weeks after sciatic nerve injury.…”
Section: G L I G L I G + a E L I G + A E L I G + A E L I G + B C G mentioning
confidence: 99%
“…Chronic neuropathic pain caused by nerve injury provokes peripheral and central sensitization. 1 That is, patients with neuropathic pain involve emotional disorders such as anxiety and depression. 2 As well, depression is an outspread chronic psychiatric disorder that interferes with social life and work performance.…”
Section: Introductionmentioning
confidence: 99%